The Legal Status of Shipwreck Cargoes as Underwater Cultural Heritage from National and International Standpoints - Arifin, Ridwan; Riyanto, Sigit; Putra, Akbar Kurnia; Wicaksono, Sonny Saptoajie; Sipahutar, Bernard (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
Shipwreck cargo or Benda Muatan Kapal Tenggelam (BMKT) in Indonesia, often referred to as underwater cultural heritage (UCH), holds significant economic potential for Indonesia, a nation prosperous in UCH sites. However, the preservation and management of these assets frequently encounter legal challenges at both national and international levels. This study examined the complex legal landscape surrounding shipwreck cargo in Indonesia, highlighting the divergent perspectives of national legislation and international norms. Indonesia's domestic laws allow for the auctioning of shipwreck cargo, which presents an opportunity for economic advancement. However, this approach clashes with the principles outlined in the Convention on Protection of the Underwater Cultural Heritage 2001, which underscore the collective heritage value of UCH objects and discourages their commercialization. This legal divergence underscores the need for Indonesia to balance its national interests with its international commitments in managing shipwreck cargo. By examining these legal intricacies, this study reveals the challenges of the coexistence of conflicting legal frameworks. It provides insights into potential strategies for harmonizing preservation efforts with commercial interests, thereby facilitating a balanced approach to the management of shipwreck cargo. By navigating these complexities, Indonesia can effectively leverage its underwater cultural heritage while fulfilling its obligations as a member of the international community.